PERAN INTERNATIONAL ATOMIC ENERGY AGENCY (IAEA) DALAM PRAKTIK PENGGUNAAN ENERGI NUKLIR UNTUK TUJUAN DAMAI DI INDONESIA - Lubis, Tanti Aulia Syafitri (Department of International Relations Universitas Pertamina, 2022)
Nuclear energy is the last alternative energy to be used on a large scale since the creation of the first nuclear fission since the end of world war II. In addition to its widely used to mitigate climate change and sustainable environmental goals, nuclear energy is also for some views considered as a symbol of a major country. To ensure its use for peaceful purposes, in 1957 the International Atomic Energy Agency (IAEA) was established, which consists of many countries in the world including Indonesia. Therefore, this article seeks to determine the IAEA's role as an international organization in the practice of using nuclear energy for peaceful purposes in Indonesia. To examine this topic, the researcher used the International Organization in International Relations as a Theoretical Framework and conducted a literature review of several previous studies related to research topics. The data and information used in this research were obtained through valid and credible books, journal articles, regulations, and internet sources. This article found that, as an international organization, the IAEA serves as a consulting body as well as a supervisor in the practice of the use of nuclear energy for peaceful purposes in Indonesia, one of which can be seen through the CPF (Country Programme Framework) document between the IAEA-Indonesia which has been signed 5 (five) times. This practice refers to the goal of achieving the optimal primary energy mix contained in Government Regulation of the Republic of Indonesia No. 79 of 2014 on National Energy Policy.